An Analysis of Code-switching Used by English Study Program Students during Teaching Practice Examination - Sarah Latifah Ahmiyul; Eliwarti; Indah Tri Purwanti (LPPM Universitas Advent Indonesia, 2026)
This study aims to investigate types, functions, and influencing factors of code-switching used by English Study Program students of FKIP Universitas Riau during their teaching practice examination. Using a qualitative case study approach, the researcher analyzed video recordings of 10 pre-service English teachers in 8 schools. Semi-structured interviews were also conducted to collect the data. A total of 499 occurrences of code-switching were found throughout the data with intra-sentential switching as the most common type (54.31%) of code-switching, followed by inter-sentential switching (42.28%) and tag-switching (3.41%). Message qualification and reiteration emerged as the two most frequently identified functions in the data. Six other functions were also found in order of frequency: elicitation, interjection, addressee specification, instruction, exemplification, and quotation. Regarding influencing factors, students’ English proficiency was revealed to be the most significant factor affecting the use of code-switching by pre-service English teachers. Additionally, the examination settings and pre-service teachers’ confidence and language competence were also identified as one of the influencing factors during the examination. The findings imply that most pre-service teachers utilize code-switching as a pedagogical tool, while also acknowledging language proficiency, both students' limited English proficiency and pre-service teachers' own linguistic constraints, as a contributing factor.